2016
DOI: 10.1038/bjc.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two WFDC1/ps20 isoforms in prostate stromal cells induces paracrine apoptosis through regulation of PTGS2/COX-2

Abstract: Background:WFDC1/Prostate stromal 20 (ps20) is a small secreted protein highly expressed within the prostate stroma. WFDC1/ps20 expression is frequently downregulated or lost in prostate cancer (PCa) and ps20 has demonstrated growth-suppressive functions in numerous tumour model systems, although the mechanisms of this phenomenon are not understood.Methods:Ps20 was cloned and overexpressed in DU145, PC3, LNCaP and WPMY-1 cells. Cellular growth, cell cycle and apoptosis were characterised. WPMY-1 stromal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Increased cytochrome c oxidase subunit II (COX-2) expression has been linked to the initiation and progression of human (11), and COX-2 has been reported to play a key role in the apoptosis of cancer cells (12). In the present study, it was found that miR-26a was significantly downregulated in prostate cancer tissues.…”
Section: Introductionmentioning
confidence: 47%
“…Increased cytochrome c oxidase subunit II (COX-2) expression has been linked to the initiation and progression of human (11), and COX-2 has been reported to play a key role in the apoptosis of cancer cells (12). In the present study, it was found that miR-26a was significantly downregulated in prostate cancer tissues.…”
Section: Introductionmentioning
confidence: 47%
“…2 (E)). Notably, WB of ps20 preparations including rps20 293F and ps20 HeLa with anti-ps20 Ab to both C-and N-terminal regions revealed the presence of the protein product of an exon 3 truncated WFDC1 mRNA described [6] and previously cloned and expressed by our lab [13] .…”
Section: Discussionmentioning
confidence: 71%
“…2 (B) and (C) arrows, and Supplementary Fig. 1 ) [13] . The third minor band at ≈15 kDa, is only detected by the C-terminal antibody in both rps20 293F and ps20 HeLa preparations ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations